Evidence of significant difference in key COVID-19 biomarkers during the Italian lockdown strategy. A retrospective study on patients admitted to a hospital emergency department in Northern Italy. - Ferrari, Davide; Carobene, Anna; Campagner, Andrea; Cabitza, Federico; Sabetta, Eleonora; Ceriotti, Daniele; Di Resta, Chiara; Locatelli, Massimo (Acta Biomedica Atenei Parmensis, 2020)
Background. The Lombardy region, Italy, has been severely affected by COVID-19. During the epidemic peak, in March 2020, patients needing intensive care unit treatments were approximately 10% of those infected. This fraction decreased to approximately 2% in the second part of April, and to 0.4% at the beginning of July. COVID-19 is characterized by several biochemical abnormalities whose discrepancy from normal values was associated to the severity of the disease. The aim of this retrospective study was to compare the biochemical patterns of patients during and after the pandemic peak in order to verify whether later patients were experiencing a milder COVID-19 course, as anecdotally observed by several clinicians of the same Hospital. Material and Methods. The laboratory findings of two equivalent groups of 84 patients each, admitted at the emergency department of the San Raffaele Hospital (Milan, Italy), during March and April respectively, were analyzed and compared. Results. White blood cell, platelets, lymphocytes and lactate dehydrogenase showed a statistically significant improvement (i.e. closer or within the normal clinical range) in the April group compared to March. Creatinine, C-reactive protein, Calcium and liver enzymes, were also pointing in that direction, although the differences were not significant. Discussion. The laboratory findings analyzed in this study were consistent with a milder COVID-19 course in the April group. After excluding several hypotheses, we concluded that our observation was likely the consequence of the lockdown strategy enforcement, which, by imposing social distancing and the use of respiratory protective devices, reduced viral loads upon infection.